Multi-objective Fuzzy optimization of plane frame systems - Keleşo?lu, Örner; Ülker, Mehmet (My University, 2006)
In this study, a multi-objective fuzzy optimization algorithm was defined and its applicability to plane frame systems was indicated. Especially it was preferred a fuzzy algorithm which is a soft calculation method, instead of hard optimization techniques. An algorithm had developed optimum design of plane frame systems by ANSYS packet programming. Fuzzy sets were added to the algorithm developed and multi-objective fuzzy optimization of plane frame systems was formed. A number of design examples are presented to demonstrate the application of the algorithm. It was has been emphasized that the multi-objective fuzzy optimization technique is an alternative method can be used in.
Düzlem çerçeve sistemlerin bulanik çok amaçli optimizasyonu
Keywords: ANSYS; Fuzzy logic; Membership function; Multiobjective optimization; Plane frame